Analysis and Modeling of the Internal Quality Audit Information System Islamic University of Kuantan Singingi - Helpi Nopriandi; Nofri Wandi Al-Hafiz; Sri Chairani (Universitas Islam Kuantan Singingi, 2025)
Internal Quality Audit (AMI) is an integral part of the Internal Quality Assurance System (SPMI) for Higher Education (Dikti), aimed at evaluating the implementation of Dikti standards. AMI plays a crucial role in examining the compliance with Dikti standards during their implementation phase. The AMI system encompasses numerous processes, including desk evaluation, visitations, requests for corrective actions, and documentation. Moreover, AMI activities ideally should be conducted annually for every Unit at Islamic University of Kuantan Singingi. Due to the limited number of auditors, it is necessary to develop an information system that enables easier monitoring and decision-making processes. This will ensure efficient and sustainable management. The unstructured archiving of audit results increases the risk of data loss and complicates information access. To address this issue, it is necessary to develop an information system using the System Development Life Cycle (SDLC) approach, which involves four major phases: planning, analysis, design, and implementation. The AMI system developed aims to support the AMI process in higher education institutions, especially at Islamic University of Kuantan Singingi (UNIKS). Before the implementation of the information system, several challenges were faced, such as difficulties in quickly obtaining information related to quality improvements for each unit periodically. This research produced a design for an information system that integrates various AMI requirements, including scheduling, self-assessment (desk evaluation) by the institution, visitations, corrective actions, and reporting.